2000
DOI: 10.1111/j.1540-8167.2000.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Surface Distribution and Response to Drugs of ST Segment Elevation in Brugada Syndrome: Clinical Implication of Eighty‐Seven–Lead Body Surface Potential Mapping and Its Application to Twelve‐Lead Electrocardiograms

Abstract: Our data indicate that recordings of leads V1-V3 of the 12-lead ECG on the parasternal second or third intercostal space would be helpful in diagnosing suspected patients with Brugada syndrome. The data suggest that Na+ channel blockers are capable of accentuating ST elevation in leads V1-V3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(133 citation statements)
references
References 22 publications
7
125
0
1
Order By: Relevance
“…It should be stressed that delineation of the J wave is sometimes tricky (second ECG in Figure 1) and that these descriptions are based on the correct placement of the precordial leads, although characteristic ECG features obtained with alternative placement of the right precordial leads in a superior intercostal space in individuals with high clinical suspicion (aborted sudden cardiac death victims, family members of patients with Brugada syndrome) may also disclose the presence of the arrhythmic substrate. 9 In select cases one may even consider rightward displacement. However, the rЈ deflection in leads V 3 R, V 4 R, etc, should be interpreted with caution.…”
Section: Electrocardiographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be stressed that delineation of the J wave is sometimes tricky (second ECG in Figure 1) and that these descriptions are based on the correct placement of the precordial leads, although characteristic ECG features obtained with alternative placement of the right precordial leads in a superior intercostal space in individuals with high clinical suspicion (aborted sudden cardiac death victims, family members of patients with Brugada syndrome) may also disclose the presence of the arrhythmic substrate. 9 In select cases one may even consider rightward displacement. However, the rЈ deflection in leads V 3 R, V 4 R, etc, should be interpreted with caution.…”
Section: Electrocardiographic Characteristicsmentioning
confidence: 99%
“…15 Clinical reports indicate that sudden death in patients with Brugada syndrome most commonly occurs during sleep, in particular during the early morning hours. 9,18 It has been suggested that there is a higher-than-normal incidence of supraventricular tachyarrhythmias, including atrial and atrioventricular reentrant tachycardia in the Brugada population. 13 Rarely, monomorphic VT is observed.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…2,4,[17][18][19] In contrast, evidence of a depolarization abnormality, especially delayed conduction in the right ventricle, has been presented. 8,[17][18][19] Depolarization abnormality is reflected in prolonged HV intervals, abnormal late potential and abnormal delayed potential in the epicardial region of the right ventricular outflow tract.…”
Section: Rate-dependent Changes In S Wave and Qrs Durationmentioning
confidence: 99%
“…2,4,[17][18][19] In contrast, evidence of a depolarization abnormality, especially delayed conduction in the right ventricle, has been presented. 8,[17][18][19] Depolarization abnormality is reflected in prolonged HV intervals, abnormal late potential and abnormal delayed potential in the epicardial region of the right ventricular outflow tract. 8,16,[20][21][22] A widening of the S wave in the right precordial leads, reflecting an underlying right ventricular conduction delay, was frequently observed in symptomatic patients and might be an important indicator of increased risk.…”
Section: Rate-dependent Changes In S Wave and Qrs Durationmentioning
confidence: 99%
“…A spontaneous coved-type ST elevation, inducible VF, and the loss-of-function SCN5A mutation are all consistent with the diagnosis of Brugada syndrome in this case that could potentially give rise to lethal arrhythmias. It was reported that some patients with Brugada syndrome, like the present case, exhibit only a coved-type ST elevationwhen the ECG is recorded from a higher intercostal space in the presence or absence of Na channel blockers 10,11 . Therefore, the proband suffered from two apparently distinct conditions: NMS and Brugada syndrome.…”
Section: Discussionmentioning
confidence: 51%